2018
DOI: 10.1111/vsu.12941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selective versus nonselective cyclooxygenase inhibitors on gastric ulceration scores and intestinal inflammation in horses

Abstract: These findings suggest that both classes of NSAID induce GI injury in horses; however, at the dosages used in this study, the COX-2 selective NSAID firocoxib resulted in less severe injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 49 publications
2
32
0
Order By: Relevance
“…Three studies have reported safety of firocoxib in adult horses, but the data are sparse . In two studies there was a lack of transparent reporting funded by the manufacturer, and in the third firocoxib was compared to doses of phenylbutazone in excess of its marketing authorisation . Although this study design makes comparisons with phenylbutazone impossible, it demonstrates that firocoxib can be associated with intestinal pathology at normal doses.…”
Section: Topical Nsaidsmentioning
confidence: 99%
“…Three studies have reported safety of firocoxib in adult horses, but the data are sparse . In two studies there was a lack of transparent reporting funded by the manufacturer, and in the third firocoxib was compared to doses of phenylbutazone in excess of its marketing authorisation . Although this study design makes comparisons with phenylbutazone impossible, it demonstrates that firocoxib can be associated with intestinal pathology at normal doses.…”
Section: Topical Nsaidsmentioning
confidence: 99%
“…Non-steroidal anti-inflammatory drugs are one of the most commonly used drugs in horses for the management of inflammation and pain of myo-arthro-skeletal or visceral origins, with flunixin meglumine traditionally being the most used NSAID for visceral pain [ 1 , 14 , 15 ]. However, this traditional, non-selective anti-inflammatory drug inhibits both COX-1 and COX-2 isoforms and has been associated with numerous side effects, including gastrointestinal ulceration and delayed mucosal healing, and renal toxicity [ 3 , 4 , 5 , 15 , 16 , 17 ]. While COX-1 is expressed constitutively and mediates the homeostasis of gut barrier function, COX-2 is induced in pro-inflammatory states, and the use of COX-2-specific NSAIDs is warranted in order to reduce the risk of complications [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Equine gastric ulcer syndrome (EGUS) is a frequently encountered disease in horses that results in high morbidity, loss of use, and high cost of diagnosis and treatment to the owner 20 . Although the causes of EGUS are unknown, NSAIDs have long been associated with inducing gastric ulcers in people and other animal species, specifically equine glandular gastric disease (EGGD) in horses 4,33 . The best approach to prevent NSAID‐induced ulcers in both people and animals is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Furthermore, we have determined that both phenylbutazone and firocoxib induce GI inflammation, gastric ulceration, and dysbiosis in horses. 4,6 In addition, specific bacteria and their metabolites have been shown to enhance intestinal barrier function in both homeostasis and disease, and conversely, loss of such bacteria can result in increased intestinal permeability. Specific to NSAID administration, evidence indicates that both probiotics and microbiota-derived metabolites can prevent NSAID-induced intestinal inflammation in people and animal models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation